Intracellular calcium in signaling human β-defensin-2 expression in oral epithelial cells - Krisanaprakornkit S. (2014)
Expression of human β-defensins is correlated with differentiation in the oral epithelium, consistent with their function as part of the epithelial antimicrobial barrier. Because calcium is a known regulator of epithelial differentiation, we tested the hypothesis that calcium concentration mediates β-defensin expression. Gingival epithelial cells were cultured in medium containing low calcium concentration (0.03 mM), then either changed to high extracellular calcium concentrations or stimulated with thapsigargin to release intracellular calcium stores in the presence or absence of BAPTA-AM, a calcium chelator. Human β-defensin-2 (hBD-2) mRNA expression was rapidly induced by thapsigargin, and more slowly induced by high extracellular calcium. Induction of hBD-2 peptide was confirmed by immunofluorescence. BAPTA-AM inhibited hBD-2 induction by both thapsigargin and calcium in a dose-dependent fashion. In addition, BAPTA-AM inhibited hBD-2 induction by a bacterial stimulant. Collectively, these findings demonstrate that intracellular calcium is a critical mediator of hBD-2 expression. Abbreviations used in this study are: BAPTA-AM, 1,2-bis(2-aminophenoxy)-ethane-N,N,N′,N′-tetra-acetic acid tetrakis (acetoxymethyl ester); DMSO, dimethylsulfoxide; F. nucleatum, Fusobacterium nucleatum; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; HBDs, human β-defensins; HGECs, human gingival epithelial cells; MAP, mitogen-activated protein; and RT-PCR, reverse-transcriptase/polymerase chain-reaction.